Effects of an afterschool program on the academic outcomes of children and youth residing in public housing neighborhoods: A quasi-experimental study. (May 2018) - Jenson, Jeffrey M.; Veeh, Christopher; Anyon, Yolanda; St. Mary, Jason; Calhoun, Molly; Tejada, Jacqueline; Lechuga-Peña, Stephanie
Abstract: Afterschool programs (ASPs) designed to increase academic performance and prevent behavior problems among young people are implemented widely. Yet few evaluations that include a comparison group have been conducted to assess the effects of these preventive interventions. This is particularly true for programs located in community settings, where research infrastructure tends to be less developed than schools. This study used a quasi-experimental design with nonequivalent comparison groups to examine the effects of a community-based ASP - located in low-income and racially segregated neighborhoods - on academic performance and school behavior problems among students in grades kindergarten to 12. The ASP's ecological program model is guided by positive youth development and a public health framework that considers risk and protective factors for academic and other behavior problems. Intervention components include academic tutoring, homework help, a manualized reading curriculum, and skill building groups that aim to enhance participants' academic and social-emotional development. Youth who participated in the ASP ( n = 418; mean age = 10.8 years; 52% female; 89% youth of color) had significantly higher levels of school attendance, a greater increase in independent reading level over the academic year, and lower odds of incurring a suspension or expulsion from school than youth in a comparison group ( n = 226; mean age = 8.99; 49% female; 94% youth of color). Participation in the ASP was also significantly related to classroom teacher ratings of proficiency in the subject areas of math and science. These findings suggest that community-based afterschool interventions have the potential to improve academic performance and school behavior among children and youth living in public housing.